Cryptanalysis of Full-Round BipBip - Wang, Jinliang; Boura, Christina; Derbez, Patrick; Hu, Kai; Li, Muzhou; Wang, Meiqin (IACR Transactions on Symmetric Cryptology, 2024)
BipBip is a low-latency tweakable block cipher proposed by Belkheyar et al. in 2023. It was designed for pointer encryption inside a new memory safety mechanism called Cryptographic Capability Computing (C3). BipBip encrypts blocks of 24 bits using a 40-bit tweak and a 256-bit master key and is composed of 11 rounds. n this article, we provide a Demirci-Selçuk Meet-in-the-Middle (DS-MITM) attack against the 11-round (full) variant that breaks the security claim of the designers.